Myocardial revascularization using the posterior intercostal arteries as grafts: anatomical variation aspect: Revaskularizacija miokarda z uporabo zadnjih medrebrnih arterij kot presadkov z vidika anatomskih variacij - Kocbek, Lidija; Anderhuber, Friedrich (Acta Medico-Biotechnica, 2021)
Purpose: The posterior intercostal arteries (PIAs) present potential alternative graft sites because of their histological, morphological, and anatomical features. We investigated the anatomical variations of the origin and course of the left fifth and right seventh PIAs, since these arteries have been demonstrated as the most suitable for in situ grafting of the coronary arteries. The aim of this study was to determine whether variations of the PIAs as grafts could influence or limit myocardial revascularization. Methods: PIAs from the origin to the mid–axillary line were dissected from 44 cadavers embalmed via Thiel’s method. The origin and course of the arteries was documented. The lengths of the common trunks, the distances to the costal angle levels, and the diameters of the arteries at the origin, at the point of division from the common trunk, and at the costal angle level were measured to calculate the diameter reduction rate. Results: Anatomical variations of the left fifth PIA were found in 25% of the cadavers. No variations were found in the right seventh PIAs. The length of the common trunk influences the length of the obtained pedicle. The PIA diameter is dependent on the origin from the aorta. The target PIA should be harvested before the costal angle level to assure a proper diameter of the conduit. Conclusion: Potential anatomical variations of the PIA must be considered when harvesting a vessel for CABG to avoid technical problems in PIA harvesting and hemodynamic changes.